KESESUAIAN PERENCANAAN DAN PENGADAAN TERHADAP KETERSEDIAAN OBAT DI INSTALASI FARMASI RSUD NOONGAN KABUPATEN MINAHASA - Sherina H. Karauwan; Gayatri Citraningtyas; Gerald E. Rundengan (PHARMACON, 2022)
ABSTRACTPlanning and procurement is a component in ensuring the quality of pharmaceutical services in the availability of drugs. This study aims to determine the description of planning and procurement of drugs at the Pharmacy Installation of RSUD Noongan in 2020 by measuring Standard Indicators. This research is descriptive in nature, taking data retrospectively, secondary data namely planning, procurement and primary data from interviews. Percentage of Allocation of Drug Procurement Fund in 2020 30%, Proportion of the number of products received from the total planned amount is 71%, Frequency of procurement of each drug item per year is 20x. The percentage of available funds is 45%, the comparison of the number of existing drug items with the number of drug items in actual use is 53%, the comparison of the number of items in each drug item with the number of drug items in actual use is 5%, the frequency of delayed payments is 29 times. 2 Indicators that cannot be measured, Frequency of incomplete orders/contracts and Percentage of quantity used from the total available quantity. The results of planning and procurement research at the Pharmacy Installation of the Noongan Hospital have not met standard indicators.Keywords : Planning, Procurement, Drug, Noongan Hospital Pharmacy InstallationABSTRAKPerencanaan dan pengadaan merupakan komponen dalam menjamin mutu pelayanan kefarmasian dalam ketersediaan obat. Penelitian ini bertujuan mengetahui gambaran perencanaan dan pengadaan obat di Instalasi Farmasi RSUD Noongan tahun 2020 dengan mengukur Indikator Standar. Penelitian ini bersifat deskriptif, pengambilan data secara retrospektif, data sekunder yaitu perencanaan, pengadaan dan data primer dari wawancara. Persentase Alokasi Dana Pengadaan Obat tahun 2020 30%, Proporsi jumlah produk diterima dari jumlah total direncanakan 71%, Frekuensi pengadaan tiap item obat per tahun 20x. Persentase dana yang tersedia 45%, Perbandingan jumlah item obat yang ada dengan jumlah item obat dalam kenyataan pemakaian 53%, Perbandingan jumlah barang dalam tiap item obat dengan jumlah barang item obat dalam kenyataan pemakaian 5%, Frekuensi tertundanya pembayaran 29 kali. 2 Indikator yang tidak dapat diukur, Frekuensi kurang lengkapnya surat pesanan/kontrak dan Persentase jumlah yang digunakan dari total jumlah tersedia. Hasil penelitian perencanaan dan pengadaan di Instalasi Farmasi RSUD Noongan belum sesuai indikator standar.Kata Kunci : Perencanaan, Pengadaan, Obat, Instalasi Farmasi RSUD Noongan